2022
DOI: 10.21037/tlcr-21-916
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages-based immune-related risk score model for relapse prediction in stage I–III non-small cell lung cancer assessed by multiplex immunofluorescence

Abstract: Background: Macrophages are critical players in regulating innate and adaptive immunity in the tumor microenvironment (TME). The prognostic value of macrophages and their heterogeneous phenotypes in non-small cell lung cancer (NSCLC) is still uncertain.Methods: Surgically-resected samples of 681 NSCLC cases were stained by multiplex immunofluorescence to examine macrophage phenotypes as well as the expression levels of program death-ligand 1 (PD-L1) on them in both tumor nest and tumor stroma, including pan-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have suggested that tumorinfiltrating macrophages are related to poor outcomes in lung cancer (17)(18)(19). However, other studies have revealed the positive role of tumor-infiltrating macrophages in lung cancer was independent risk factor for NSCLC progression (20)(21)(22). The function of macrophages in the prognosis of lung cancer is still controversial, and further investigation is required to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that tumorinfiltrating macrophages are related to poor outcomes in lung cancer (17)(18)(19). However, other studies have revealed the positive role of tumor-infiltrating macrophages in lung cancer was independent risk factor for NSCLC progression (20)(21)(22). The function of macrophages in the prognosis of lung cancer is still controversial, and further investigation is required to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have noted correlations between immune cell levels and DFS. In particular, a study by Wu et al [ 32 ] showed that higher levels of CD68 and M1 macrophages are associated with worse DFS ( P < 0.0001). Based on the results obtained, a nomogram was constructed that included age and sex, the presence of visceral pleural invasion, the number of lymph nodes removed, clinical stage and the immune-related risk assessment nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…We found that LUSCs with low and high MSS estimates corresponded to tumours with immunoreactive and immunosuppressive TMEs, respectively. Recent findings by Wu et al revealed macrophage numbers were moderately correlated with the level of PD‐L1, CD133, and CD8 [ 66 ]. Consistently, our findings suggest that MSS and immunological indicators may be related.…”
Section: Discussionmentioning
confidence: 99%